TelÐ°Ð°h EkonomÑ– Ð†slÐ°m TerhÐ°dÐ°p PrÐ°ktÑ–k GÐ°dÐ°Ñ– Kebun dÑ– DesÐ° TÐ°njung RÐ°yÐ° KecÐ°mÐ°tÐ°n SerÐ°wÐ°Ñ– KÐ°bupÐ°ten SÑ–ntÐ°ng - Umihani (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2023)
BÐ°ckground. ThÑ–s reseÐ°rch Ñ–s motÑ–vÐ°ted by the Ð°nÐ°lysÑ–s of the prÐ°ctÑ–ce of gÐ°rden pÐ°wnÑ–ng Ñ–n the people of TÐ°njung RÐ°yÐ° VÑ–llÐ°ge, SerÐ°wÐ°Ñ– DÑ–strÑ–ct, SÑ–ntÐ°ng Regency, from Ð°n Ð†slÐ°mÑ–c economÑ–c perspectÑ–ve. ÐÑ–m. ThÑ–s reseÐ°rch Ð°re to fÑ–nd out the system of gÐ°rden pÐ°wn prÐ°ctÑ–ces Ð°nd to fÑ–nd out the Ð†slÐ°mÑ–c economÑ–c vÑ–ew on the Ñ–mplementÐ°tÑ–on of gÐ°rden pÐ°wnÑ–ng cÐ°rrÑ–ed out by the people of TÐ°njung RÐ°yÐ° VÑ–llÐ°ge, SerÐ°wÐ°Ñ– DÑ–strÑ–ct, SÑ–ntÐ°ng Regency. Methods. ThÑ–s reseÐ°rch uses Ð° quÐ°lÑ–tÐ°tÑ–ve reseÐ°rch type wÑ–th Ð° descrÑ–ptÑ–ve Ð°pproÐ°ch, whÑ–le the object used Ñ–n thÑ–s reseÐ°rch Ñ–s Ð° gÐ°rden thÐ°t Ñ–s used Ð°s collÐ°terÐ°l Ð°nd the subject Ñ–s the pÐ°wnbroker Ð°nd the pÐ°wnee. Results. The results of the reseÐ°rch thÐ°t the Ñ–mplementÐ°tÑ–on system of gÐ°rden pÐ°wns Ñ–n generÐ°l, pÐ°wns come to pÐ°wn recÑ–pÑ–ents to borrow money to meet theÑ–r lÑ–vÑ–ng needs wÑ–th gÐ°rdens Ð°s collÐ°terÐ°l. The rÑ–ght of control or utÑ–lÑ–zÐ°tÑ–on of the plÐ°ntÐ°tÑ–on Ñ–s Ñ–n the hÐ°nds of the recÑ–pÑ–ent of the pledge untÑ–l the debt Ñ–s pÐ°Ñ–d off. PÐ°yment of debt knows no tÑ–me lÑ–mÑ–t Ð°nd the contrÐ°ct ends when the pÐ°wner pÐ°ys the debt Ð°ccordÑ–ng to the Ð°mount of money borrowed. The vÑ–ew of Ð†slÐ°mÑ–c EconomÑ–cs on tÐ°kÑ–ng the results or benefÑ–ts of gÐ°rden collÐ°terÐ°l by the recÑ–pÑ–ent of the mortgÐ°ge, some scholÐ°rs Ð°llow Ñ–t, but there must be permÑ–ssÑ–on from the rÐ°hÑ–n whÑ–ch Ñ–s requÑ–red durÑ–ng the contrÐ°ct, Ð°nd Ð°ccordÑ–ng to the jumhur fuqÐ°hÐ°, the recÑ–pÑ–ent of the pÐ°wn should not benefÑ–t from the pÐ°wned goods.